2007
DOI: 10.1007/s10350-007-0286-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA Stool Test for Colorectal Cancer: Hypermethylation of the Secreted Frizzled-Related Protein-1 Gene

Abstract: The results indicate that this DNA stool test of hypermethylation of the secreted frizzled-related protein-1 promoter is a sensitive and specific method. It has the potential of a clinically useful test for the early detection of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 40 publications
(29 reference statements)
0
38
0
Order By: Relevance
“…Apart from SFRP2, methylation of the SFRP1 gene seems to be a suitable marker for colorectal cancer in fecal DNA; Zhang et al reported a sensitivity of 84% and specificity of 86% for this marker. However, methylation of the SFRP1 gene increased with tumor stage, suggesting that the SFRP1 marker preferentially detects colorectal cancers at higher UICC stages [53]. To identify new potential markers for aberrant DNA methylation, Mayor et al analyzed the extent and prevalence of long-range epigenetic silencing at the chromosomal region 2q14.2 and identified the gene EN1 as a target of this phenomenon.…”
Section: Stoolmentioning
confidence: 98%
“…Apart from SFRP2, methylation of the SFRP1 gene seems to be a suitable marker for colorectal cancer in fecal DNA; Zhang et al reported a sensitivity of 84% and specificity of 86% for this marker. However, methylation of the SFRP1 gene increased with tumor stage, suggesting that the SFRP1 marker preferentially detects colorectal cancers at higher UICC stages [53]. To identify new potential markers for aberrant DNA methylation, Mayor et al analyzed the extent and prevalence of long-range epigenetic silencing at the chromosomal region 2q14.2 and identified the gene EN1 as a target of this phenomenon.…”
Section: Stoolmentioning
confidence: 98%
“…29 SFRP1 methylation in stool DNA has already shown to be useful in early detection of colorectal carcinomas. 30 With this approach, SFRP4 would appear to be a good candidate for screening for precursors in the serrated neoplasia pathway. Further study is needed to elucidate WNT/bcatenin signal activation in this pathway in more detail and to confirm clinical utility of such markers because the number of cases of SSA/P with dysplastic (malignant) transformation was limited in the present study.…”
Section: Modern Pathology (2015) 28 146-158mentioning
confidence: 99%
“…We have identified a cohort of 43 genes epigenetically silenced in GBM with associated promoter hypermethylation. These promoter hypermethylation patterns have also been shown to be stable, tissue-and tumor specific, and readily detectable by sensitive PCR methods Ibanez de Caceres et al, 2004;Tan et al, 2007;Zhang et al, 2007). This comprehensive identification of epigenetically regulated genes in GBM holds considerable promise for early detection, diagnosis and, potentially, prognosis in response to therapy.…”
Section: Discussionmentioning
confidence: 93%